2012
DOI: 10.12934/jkpmhn.2012.21.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-esteem, Emotional Intelligence and Social Support on College Adjustment in First Year Nursing College Students

Abstract: Purpose:The purpose of this study was to investigate the effects of self-esteem, emotional intelligence and social support on college adjustment in first year students in nursing. Methods: The participants were 270 first year nursing college students. Data were collected from September 5 to 12, 2011 and analyzed using descriptive statistics, t-test, ANOVA, Pearson correlation coefficients and multiple regression with SPSS 18.0. Results: A positive correlation was found between college adjustment and self-estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…When the studies conducted in the field are examined, it is seen that many studies have been conducted on the effect of emotional intelligence on the academic success of teachers, teacher candidates and students, adaptation to life, personality formation and its relationship with various variables (Engelberg & Sjöberg, 2004;Gursimsek, Ekinci, & Selcioglu, 2008;Humphrey, Curran, Morris, Farrell, & Woods, 2007;Ishak, Jdaitawi, Ibrahim, & Mustafa, 2011;Jung & Chung, 2012;Kirimoglu, Yeniad, & Shepherd, 2014;Koçoglu, 2011;Perera & DiGiacomo, 2015;Pinarcik, Sali, & Altindis , 2016).…”
Section: Related Researchmentioning
confidence: 99%
“…When the studies conducted in the field are examined, it is seen that many studies have been conducted on the effect of emotional intelligence on the academic success of teachers, teacher candidates and students, adaptation to life, personality formation and its relationship with various variables (Engelberg & Sjöberg, 2004;Gursimsek, Ekinci, & Selcioglu, 2008;Humphrey, Curran, Morris, Farrell, & Woods, 2007;Ishak, Jdaitawi, Ibrahim, & Mustafa, 2011;Jung & Chung, 2012;Kirimoglu, Yeniad, & Shepherd, 2014;Koçoglu, 2011;Perera & DiGiacomo, 2015;Pinarcik, Sali, & Altindis , 2016).…”
Section: Related Researchmentioning
confidence: 99%
“…Research examining college students and nurses has found that perceived support in personal relationships is positively correlated with psychological well‐being and negatively correlated with stress scores and psychological problems (Ersoy‐Kart, ; Jeon, ; Seo, Choi, & Jo, ). Moreover, support from parents and teachers facilitates social adaptation to university life and support from friends improves emotional adaptation (Jung & Chung, ; Lee, Moon, & Park, ). Cha and Lee () found that nursing students experience less stress in relationships with family or teachers than general students; however, no studies have compared nursing and general students regarding the effect of social support on anger.…”
Section: Introductionmentioning
confidence: 99%
“…인 지적 정서조절전략은 최근 정신건강 관련 분야에서 심리적 안 녕감을 유지하는 주요 개념으로 활발한 연구가 이루어지고 있 는 추세이며 (Aldao & Nolen-Hoeksema, 2010;Choi & Kim, 2012;Lee & Chae, 2012;Öngen, 2010;Shim, An, & Kim, 2011;Zlomke & Hahn, 2010) 나 간호대학생 대상의 28점 (Jung, Cho, & Chung, 2012 …”
unclassified